An assessment of the antibacterial efficacy of secondary metabolites derived from Bacopa monnieri (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The present study aimed to examine the secondary metabolites of Brahmi. The ethanol and methanolic extractive value of Bacopa monnieri (L) was found to be 9.98%. and 9.02%, respectively. The physiochemical analysis revealed the total ash value to be 14%. The examination of Bacopa monnieri (L) revealed the presence of notable secondary metabolites such as carbohydrates, proteins, steroids, glycosides, flavonoids, alkaloids, and tannins in both methanolic and ethanolic extracts. The presence of three primary saponins, specifically bacoside A3, bacopaside II, and bacopaside X, in the ethanolic extract was determined using the HPLC technique. Subsequently, the aggregate amounts of these saponins were calculated. The concentration of bacoside A in the extract described in this process was higher than that of the total saponins. Furthermore, the antibacterial effectiveness of Bacopa monnieri (L) was evaluated by employing ethanolic extracts against two strains of gram-positive bacteria (S.aureus and B.subtillis) and two strains of gram-negative bacteria (E.coli and H.pyroli) at concentrations of 1.5 mg/ml, 3 mg/ml, 6 mg/ml, and 12 mg/ml. The extract did not exhibit any antibacterial action at a concentration of 1.5 mg/ml. Nevertheless, the ethanolic extract at a dosage of 12mg/ml demonstrated significant antibacterial activity. The greatest zone of inhibition was seen against S.aureus (17.88±0.02), with E.coli (17.75±0.02) showing the second highest zone of inhibition. Hence, Bacopa monnieri possesses the capacity to be assessed as an antibacterial agent due to bacosides. Nevertheless, additional preclinical and clinical investigations will be necessary in the future.